MUSIC-3D Approach and Kraljic’s Purchasing Portfolio Model in Determining PT Semen Padang's Spare Parts Procurement Strategy - Wirdianto, Eri; Rahman, Anatachia; Milana, Milana (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
MRO (Maintenance, Repair, Operations) is a type of inventory to maintain the smooth production process. The large number of spare parts to be managed and their lumpy usage patterns are a challenge in the procurement process. This research aims to determine the classification and procurement strategy for each spare parts classification group in PT. Semen Padang. The classification method used is MUSIC-3D which consists of ABC, FNS and SDE. This classification produces 27 spare parts groups which are mapped into Kraljic's Matrix. From the mapping results, the 27 groups are spread into four quadrants. Strategic Quadrant with recommendations for partnership contract types and long-term relationships, Leverage Quadrant with recommendations for partnership or call of contract types and short-term relationships, Bottleneck Quadrant with recommendations for call of contract types and short-term relationships, Non-Critical Quadrant with recommendations for spotting purchase in the purchasing process. MRO (Maintenance, Repair, Operations) merupakan salah satu jenis persediaan untuk menjaga kelancaran proses produksi. Banyaknya jumlah suku cadang yang dikelola serta pola pemakaiannya yang lumpy menjadi tantangan dalam proses pengadaannya. Penelitian ini bertujuan untuk menentukan klasifikasi dan strategi pengadaan untuk setiap kelompok klasifikasi suku cadang di PT. Semen Padang. Metode klasifikasi yang digunakan adalah MUSIC-3D yang terdiri dari ABC, FNS dan SDE. Klasifikasi tersebut menghasilkan 27 kelompok suku cadang yang dipetakan ke dalam Kraljic’s Matrix. Dari hasil pemetaan, ke 27 kelompok suku cadang tersebar ke dalam empat kuadran. Kuadran Strategic dengan rekomendasi tipe kontrak partnership dan hubungan jangka panjang, Kuadran Leverage dengan rekomendasi tipe kontrak partnership atau call of contract dan hubungan jangka pendek, Kuadran Bottleneck dengan rekomendasi tipe kontrak call of contract dan hubungan jangka pendek, Kuadran Non–Critical dengan rekomendasi melakukan spot purchase dalam proses pembeliannya.